Artificial Intelligence - Blessing or Curse in Dentistry? - A Systematic Review - Y Greeshma Vani; Suma B. Chalapathy; Pallavi Pandey; Shailendra K. Sahu; A Ramesh; Jayashree Sajjanar (Journal of Pharmacy and Bioallied Sciences)
This systematic review examines the diverse applications of AI in all areas of dentistry. The search was conducted using the terms “Artificial Intelligence,” “Dentistry,” “Machine learning,” “Deep learning,” and “Diagnostic System.” Out of 607 publications analyzed from 2010 to 2024, only 13 were selected for inclusion based on their relevance and publication year. AI in dentistry offers both advantages and challenges. It enhances diagnosis, therapy, and patient outcomes through complex algorithms and massive datasets. However, issues such as data privacy, dental professional job displacement, and the necessity for thorough validation and regulation to ensure safety and efficacy remain significant concerns.